Vaccination Confidence among Healthcare Workers: Results from Two Anamnestic Questionnaires Adopted in the COVID-19 and Influenza Campaign - Ihab Mansour; Giulia Collatuzzo; Vittoria De Pasquale; Ilenia Mirra; Catalina Ciocan; Alessandro Godono; Enrico Pira; Paolo Boffetta (Vaccines, 2022)
Background: Following the announcement of the development of COVID-19 vaccines, hesitancy about the safety of vaccinations and their side effects have spread, despite having the approval of international drug agencies. The aim of this study was to test the hypothesis that concern about side effects may have led people to fill out the COVID-19 anamnestic vaccine questionnaire with greater attention compared to the similar instrument used for the influenza vaccination. Methods: We analyzed vaccination questionnaires of 218 healthcare workers (HCWs) who underwent both COVID-19 and influenza vaccines in 2020/2021. Outcomes included self-reported allergies, chronic pharmacological treatments, and chronic diseases. We tested the difference in prevalence, analyzed differences using the kappa statistics and concordance correlation, and explored factors associated with differences in reporting. Results: HCWs reported more allergies to substances other than drugs and a higher prevalence of chronic drug intake in the COVID-19 questionnaires than in the influenza ones. Technical staff reported more drug allergies than physicians, and other HCWs reported more outcomes than physicians in the COVID-19 questionnaire. Conclusions: We found that this population of HCWs reported higher conditions during the 2020 COVID-19 vaccination campaign compared to that of the influenza vaccine. The identification of socio-demographic characteristics of the less vaccine-confident HCWs could help in planning targeted interventions to enhance vaccine adherence.